What takes the wind out of their sails? A~micro-foundational perspective of challenges for building dynamic capabilities towards digital business model innovation - Daliborka Witschel; Julian Müller; Kai-Ingo Voigt (Schmalenbach Journal of Business Research (SBUR), 2023)
While dynamic capabilities (DCs) are recognized as an important enabler of digital transformation, research lacks knowledge about the underlying challenges and adequate responses of building these capabilities. More specifically, this study aims to shed light into successful digital business model innovation (BMI) by adopting a micro-foundational approach that covers both challenges and successful measures on this path for incumbent industrial firms. Therefore, six case studies building on qualitative empirical research are analyzed that either focus on Internet of Things (IoT)-driven platform BMI or software as a service (SaaS) BMI. The results offer a variety of insights regarding challenges and respective responses. These findings are attributed to DCs and its subdimensions of sensing, seizing and transforming, further revealing the interplay of various factors for specific contexts. Additionally, the study reveals that many challenges and thus required responses are the result of individuals, processes, and structures.
Keywords: L00; M10; M19; O32; O33; 650; Digital Business Model Innovation; Digital Platforms; Digital transformation; Dynamic capabilities; Micro-foundations; Qualitative Empirical Research